Adhesive Strength in Dentin Conditioned with 18% Ethylenediaminetetraacetic Acid versus 35% Phosphoric Acid: In Vitro Study with 1-Year Artificial Aging - Alcántara-Obispo, Esther (2022)
The success and longevity of a resin composite restoration is determined by its good bonding to the tooth structure, with the adhesion being a challenge to dentin due to its complexity and structural heterogeneity. The present study aimed to compare the adhesive strength of dentin conditioned with 18% ethylenediaminetetraacetic acid (EDTA) versus 35% phosphoric acid (H3PO4) in human premolars. Materials and Methods: This in vitro experimental study was performed on 40 human premolars. The occlusal thirds were sectioned and randomly placed into four groups according to the type of dentin conditioning: Group 1 (control), Group 2 (18% EDTA), Group 3 (35% H3PO4) and Group 4 (18% EDTA plus 35% H3PO4). Then, 10,000 thermocycles between 5 +/− 2 °C and 55 +/− 2 °C were applied. Adhesive strength was tested by shearing with a digital universal testing machine at a crosshead speed of 0.75 mm/min. The values obtained were analyzed in megapascals (MPa). The mean and standard deviation were used as measures of central tendency and dispersion. In addition, a one-factor intergroup ANOVA test was applied with Tukey’s post hoc test considering a significance level of p < 0.05. Results: The 18% EDTA and 18% EDTA plus 35% H3PO4 showed significantly higher adhesive strength compared to the control group that did not receive dentin conditioning (p = 0.047 and p < 0.001, respectively). However, the group conditioned with 18% EDTA did not present significant differences compared to the group conditioned with 35% H3PO4 (p = 0.997). In addition, the group conditioned with 18% EDTA plus 35% H3PO4 showed significantly higher adhesive strength compared to the groups conditioned with 18% EDTA (p = 0.002) and 35% H3PO4 (p = 0.001). Conclusion: The adhesion of bulk fill resin composite to dentin was favorable when preconditioning was performed using 18% EDTA followed by 35% H3PO4. In contrast, when both etchants were used separately, the bulk fill resin composite showed similar bond strength values in both cases, but significantly lower compared to their sequential application.